Where is Russia heading? - Natalija Pliskevič (Migracijske i etničke teme, 1999)
The author examines the proceedings from the collection Where is Russia Heading? (= Куда идёт Россия?), published between 1994 and 1998 in connection with the international symposium held under this name each year in Moscow. The symposia and their proceeding, involving leading Russian and foreign experts, were significant in that they encompassed a wide range of themes – social, economic, political, legislative, cultural and other transformations that have been occurring in Russia during the past decades. The author, however, limits her review to contributions dealing with ethno-political and socio-cultural transformations in Russia. She concludes that the question – “Where is Russia heading?” – still remains open to answers.